2013
DOI: 10.4103/0971-6580.111549
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low level microwave radiation induced deoxyribonucleic acid damage vis-à-vis genotoxicity in brain of fischer rats

Abstract: Background:Non-ionizing radiofrequency radiation has been increasingly used in industry, commerce, medicine and especially in mobile phone technology and has become a matter of serious concern in present time.Objective:The present study was designed to investigate the possible deoxyribonucleic acid (DNA) damaging effects of low-level microwave radiation in brain of Fischer rats.Materials and Methods:Experiments were performed on male Fischer rats exposed to microwave radiation for 30 days at three different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
0
7
0
1
Order By: Relevance
“…The brain has a high metabolic rate, making it more prone to damage by ROS and oxidative damage compared to other organs [ 69 ]. Excessive amounts of ROS in tissues may lead to necrosis, the death of neurons and neuronal damage in brain tissue, as well as to neurological disorders such as Alzheimer’s disease, spinal cord injury, multiple sclerosis, and epilepsy [ 70 ] ( Fig. 2 ).…”
Section: Emf-related Oxidative Stress and Effects On Tissuementioning
confidence: 99%
“…The brain has a high metabolic rate, making it more prone to damage by ROS and oxidative damage compared to other organs [ 69 ]. Excessive amounts of ROS in tissues may lead to necrosis, the death of neurons and neuronal damage in brain tissue, as well as to neurological disorders such as Alzheimer’s disease, spinal cord injury, multiple sclerosis, and epilepsy [ 70 ] ( Fig. 2 ).…”
Section: Emf-related Oxidative Stress and Effects On Tissuementioning
confidence: 99%
“…Previous investigations indicated that radiations can induce several damages at DNA level (20), changes in the structure and functions of plasma membrane [i.e., NADH (nicotinamide adenine dinucleotide) oxidase and phosphatidylserine] (21), Ca 2+ signaling and NMDA (Nmethyl-d-aspartic acid) receptor functions (22), voltagegated calcium channels (23), and oxidative stress (10). These changes could cause cellular and organ dysfunctions.…”
Section: Ionizing /Non-ionizing Radiation and Cell Functionmentioning
confidence: 99%
“…Components of heredity substances of eukaryote cells are susceptible to oxidative damages; pyrimidines are more susceptible to oxidative damages than purines and Various studies showed that exposure to ionizing radiation directly and indirectly via generating singlet oxygen, induce lesions in cellular DNA through deletions, mutations and other lethal genetic effects (20). The 8-hydroxy-2-deoxyguanosine (8-OH-2-deoxyguianosine) is a common byproduct of DNA oxidation considered as a key biomarker of oxidative DNA damage (35).…”
Section: Radiation Ros and Dna Damagementioning
confidence: 99%
See 1 more Smart Citation
“…There is growing serious concern that the exponentially increased exposure to RF-EMF from mobile phones might lead to adverse health effects [ 30 ]. Cell phones are popular communication devices that emit low levels of RF-EMF.…”
Section: Introductionmentioning
confidence: 99%